1990
DOI: 10.3109/00498259009046835
|View full text |Cite
|
Sign up to set email alerts
|

Species variation in the response of the cytochrome P-450-dependent monooxygenase system to inducers and inhibitors

Abstract: 1. In the safety evaluation of drugs and other chemicals it is important to evaluate their possible inducing and inhibitory effects on the enzymes of drug metabolism. 2. While many similarities exist between species in their response to inducers and inhibitors, there are also important differences. Possible mechanisms of such variation are considered, with particular reference to the cytochrome P-450 system. 3. Differences in inhibition may be due to differences in inhibitory site of the enzyme involved, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 72 publications
1
39
1
1
Order By: Relevance
“…However, the difference may exist for a specific enzyme and organic solvent. The active site as well as incubation binding site may be different among different species (Boobis et al, 1990), as highlighted in a previous study (Eagling et al, 1998). The detailed difference for the organic solvent effects on P450 enzyme activities between rat and human needs further study.…”
Section: Resultsmentioning
confidence: 99%
“…However, the difference may exist for a specific enzyme and organic solvent. The active site as well as incubation binding site may be different among different species (Boobis et al, 1990), as highlighted in a previous study (Eagling et al, 1998). The detailed difference for the organic solvent effects on P450 enzyme activities between rat and human needs further study.…”
Section: Resultsmentioning
confidence: 99%
“…Boobis et al (1990) suggested the following three possible reasons for species differences in the effects of chemical inhibitors on drug metabolism in vitro: 1) the active site differs in species, 2) the isoform-catalyzing metabolism differs in species, 3) the inhibition is not via direct competition at the active site and the inhibitory site differs in species. In the present study, cDNA-expressed systems were used for screening of selectivity and comparative potency of several inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Animal studies may give important information on herb -CYP interactions, but interspecies variations in the substrate specificity, catalytic features, and amino acid sequences of CYPs may cause difficulty in extrapolating animal data to humans (Boobis et al, 1990;Lewis et al, 1998;Lin, 1995). For example, chlorzoxazone 6-hydroxylation is extensively catalyzed by CYP2E1 in humans (Halpert et al, 1994;Murray and Reidy, 1990), but also by CYP1A2 and CYP3A1 in rats (Kobayashi et al, 2002).…”
Section: Herb-cyp Interactions 41mentioning
confidence: 99%